DESTRUCTION OF HUMAN TRAFFICKING FROM AN ISLAMIC PERSPECTIVE (AN INTERPRETIVE STUDY OF DIGNITY AND ETHICS): DESTRUCTION OF HUMAN TRAFFICKING PERSPEKTIF ISLAM (STUDI PENAFSIRAN ATAS MARTABAT DAN ETIKA) - Hafiz Fachriansyah; Uqbatul Khoir Rambe (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to examine in depth the Islamic view of the phenomenon of human trafficking by highlighting aspects of human dignity and ethics through a thematic interpretation approach to the verses of the Qur'an. Human trafficking is understood as a serious violation of human values and universal ethical principles. Using a qualitative approach based on library research, this study analyzes the verses of the Qur'an related to human creation, justice, the prohibition of exploitation, and examines the interpretation of classical and contemporary mufassir. Key findings show that Islam unequivocally rejects all forms of human exploitation, including sexual exploitation, forced labor, forced marriage, child trafficking and illegal organ sales. This research contributes to strengthening the framework of Islamic ethics as a normative source in supporting policies to protect human rights and dignity, as well as social advocacy strategies. The implications of the study show the importance of integration between Islamic values and the international legal framework in formulating preventive and transformative responses to human trafficking. This research also opens up space for the development of social fiqh and critical education based on Islamic values as an effort to empower the community. Further research is needed to explore the role of religious institutions in the structural implementation of these values.